Interaction of phosphorus and water supply regulates the maize root system and phosphorus-use efficiency - Wang, Maoying; Xu, Jie; Lyu, Yang; Luo, Mengjie; Sun, Yucui; Ye, Shengjia; Cheng, Lingyun; Rengel, Zed; Shen, Jianbo (Frontiers in Plant Science, 2026)
IntroductionImproving phosphorus (P)-use efficiency (PUE) while increasing crop yield is one of the greatest challenges in sustainable P management for sustainable agriculture. Types of P fertilizers and soil water supply impact P availability and crop growth, but how to optimize P fertilizer and water supply to enhance the foraging capacity of roots for P remains unclear. This study was aimed at characterizing the effects of different combinations of P fertilizers and water supply on maize growth, root properties and PUE in calcareous soil.MethodsA pot experiment with four P fertilizers [monoammonium phosphate (MAP), diammonium phosphate (DAP), ammonium polyphosphate (APP) and urea phosphate (UP)] was conducted under well-watered (watered) and water-deficit (dry) conditions using maize (Zea mays L.) in a greenhouse during the seedling stage.ResultsThe interaction between P fertilizers and water supply significantly promoted the growth and P uptake of maize by modifying the root morphological and physiological traits. MAP and APP exhibited greater (by up to 62%) total root length in the watered than the dry treatments, resulting in a significant increase in the efficiency of root P acquisition. The APase activity in the rhizosphere soil of MAP and DAP declined (by 37%-62%) significantly, and the rhizosphere soil pH in the DAP treatment was 0.4 units lower in the watered than the dry treatments. APP improved the soil P availability more than the other P fertilizers (17%-41% higher in soil Olsen-P concentration) regardless of water supply.ConclusionOptimal combination of P fertilizers and water supply promotes maize growth and PUE due to stimulating the root capacity to forage for nutrient and water resources by regulating the root morphological and physiological traits. Engineering root/rhizosphere by manipulating the interactions of P fertilizer types and water supply can improve nutrient use-efficiency and sustainable crop production.